Breathing Clean : Considering the Switch to Natural Gas Buses - Kojima, Masami (Washington, DC: World Bank, 2013)
In response to emerging epidemiological evidence of the toxicity of diesel vehicular emissions, there is growing interest in substituting conventional diesel with much cleaner natural gas in cities where ambient concentrations of particulate matter are markedly higher than what is internationally considered acceptable. This paper compares the performance of natural gas and conventional diesel buses, and outlines the barriers to the adoption of natural gas buses in developing countries. In the absence of emissions standards that effectively require natural gas, natural gas-fueled buses are unlikely to be adopted because they are more expensive to operate relative to diesel buses. The social case for replacing diesel with natural gas a fuel for buses rests on environmental grounds. If a local government decides that the reduction in air pollution associated with the substitution of conventional diesel with natural gas for use in buses is worth the cost, then it needs to adopt policies to encourage the switch to natural gas. These might include emissions standards for buses, or fuel and vehicle taxes that reflect marginal social costs. The contribution of exhaust emissions from buses to the ambient concentrations of harmful pollutants needs to be quantified so that associated health damage costs can be estimated.